PEMBUATAN SISTEM KENDALI POSISI AUTOFOKUS EKSPERIMEN LENSA DENGAN MOTOR LANGKAH - Gunadi, Isnain; Gernowo, Rahmat; Adi, Kusworo (BERKALA FISIKA, 2015)
The automatic lens experiment with stepper motor position control has been made. Main component of this device are stepper motor which move the lens and screen. Microcontroller is contens the programs of motor movement controller. The screen contain of Light Dependent Resistor (LDR) as voltage sensor. This image will focused when the voltage in the screen is maximum. The result of test show that the automatic measurement is more accurate than manual measurement.Keywords: Auto-Fokus, LDR, IPMC, LSW, EAPs, VCM